Pemberdayaan Umkm Desa Takaras melalui Pemasangan Spanduk Informasi dan Pendaftaran Lokasi di Google Maps - Nor Hidayah; Yudhojon Novembero; Ida Bagus Suryanatha (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The empowerment program for Micro, Small, and Medium Enterprises (MSMEs) in Takaras Village, Manuhing Subdistrict, Gunung Mas Regency, was carried out to address the problem of low business visibility due to limited promotional media and minimal use of digital technology. Most MSMEs still relied on traditional word-of-mouth promotion, which restricted market reach and reduced competitiveness. To overcome this, the KKN Reguler I Team Group 55 of the University of Palangka Raya implemented activities consisting of informational banner installation and business location registration on Google Maps. The methods included field surveys, banner design planning using simple digital tools, direct assistance in location registration, and banner installation at business sites. The program involved 26 MSMEs, of which 18 received banner support. The installation of banners provided a clearer visual identity for each business, while the use of Google Maps significantly improved consumer accessibility to business locations and services. The results showed that the combination of offline (banners) and online (Google Maps) promotion was effective in increasing product visibility, attracting more customers, and strengthening consumer trust. This initiative also encouraged MSMEs to adopt digital technology in their marketing strategies. Overall, the program made a tangible contribution to the digital transformation of local MSMEs and laid the foundation for sustainable community economic competitiveness